Governing Dynamics and Superfragility: Liberal Political Economists as Order Guardians - Stefan Kolev (Ludwig-Erhard-Forum für Wirtschaft und Gesellschaft (LEF), 2024)
This paper pursues two goals. First, to reflect on how historical Ordnungsökonomik (Economics of Order) illuminates the politico-economic crises in today's Western democracies via the increasing parallels to the fragilities and fractures of the 1930s. Second, based on these historical inspirations, to come closer to a modern Ordnungsökonomik targeted specifically at today's crises. The three-step approach consists of an anamnesis ("crisis burger"), a diagnosis ("anxiety from over-dynamics"), and a therapy ("fixed points towards order security"). The paper revisits the role of liberal political economists as order guardians amid what the paper calls superfragility, a context in which citizens radically lose trust and unsubscribe from the order, making the trust-enhancing role of liberal political economists existential for the order.
Keywords: A11; B25; B41; H11; P16; 330